Model Hubungan Empowering Leadership, Spiritual Value, Co-Worker Incivility dan Work Engagement - Ikhwan Ikhwan (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study aims to examine the relationship model of empowering leadership, spiritual value, incivility, and work engagement. A total of 396 participants (57 percent women) were sampled and hierarchical regression techniques were used to test the hypothesis. The results showed that empowering leadership and organizational spiritual values had a significant impact on work engagement, however, incivility was not shown to moderate the relationship between empowering leaders and work engagement. The practical implications that can be given from these findings are: leadership styles that lead to employee empowerment can have a unique effect on employees' work attitudes and behavior so that companies need to provide leaders and managers with training and development programs to develop leadership models that can act effectively and willingly. delegated authority.